Factores de riesgo en personas privadas de libertad en cárceles peruanas por delitos patrimoniales - Florentini Castañeda, Marlon Wilbert (2021)
This research is aimed at exploring the risk factors of the personal, family and social context, present in the life history of people deprived of liberty, men and women sentenced for crimes against property. For this purpose, a non-experimental, cross-sectional, quantitative empirical study with a descriptive-comparative scope was designed. For the investigation, a sample of inmates was selected, made up of sentenced persons from the ordinary closed regime prisons Lurigancho and Callao, as well as a sample of inmates from the common Chorrillos penitentiary, making a total of 358 people. The data collection instrument was developed based on the psychosocial file applicable by the National Penitentiary Institute of Peru and was applied by direct interview with each member of the sample. The data were processed using the SPSS statistical program. The results show that both female and male inmates present similar risk factors in individual, family, educational and social contexts throughout their life history. These factors should be taken into account in crime and crime prevention policies and programs.